Change in basic need frustration in relation to perfectionism, anxiety, and performance in elite junior performers - Haraldsen, H. M.; Solstad, B. E.; Ivarsson, A.; Halvari, H.; Abrahamsen, F. E. (Scandinavian Journal of Medicine & Science in Sports, 2020)
The present study examined whether there were different growth profiles in basic need frustration in elite junior performers over a nine-month period. Subsequently, we examined whether the identified growth profiles differed in their levels of perfectionistic strivings and evaluative concerns measured at baseline and, additionally, whether they were associated with higher or lower levels of anxiety and perceived performance level in the end of the period. A sample of 259 (Mage = 17.31; SDage = 0.97) elite junior performers from sports and performing arts completed an online questionnaire to report their self-ratings of the study variables. The analyses were conducted using growth mixture modeling in Mplus 8.0. Two main contrasting growth profiles were identified in each of the basic need frustration. Perfectionistic strivings were overall higher than evaluative concerns, but did not differ between the growth profiles. Conversely, evaluative concerns differed significantly between the identified growth profiles. Higher levels of evaluative concerns were associated with the most maladaptive growth profiles. Indeed, elite junior performers, who experienced moderate and increasing levels of competence and autonomy frustration, reported higher levels of anxiety and lower levels of perceived performance level than those who reported low and decreasing levels of competence and autonomy frustration. Based on these findings, evaluative concerns and basic need frustration appear to play key roles in the development of maladaptive motivational processes over time.